Development, Characterization and Evaluation of Anti-Inflammatory Drug Loaded Snedds for Gout - F Mehta, Farhad; Patel, Meenakshi; Shivani, Shivani; Murari Lal Verma, Abhay; Rastogi, Sameer; Sarkar, Bishal; Kumar, Sunil; Kumari, Sabita (Journal of Neonatal Surgery, 2025)
A hydrophobic and highly permeable medication, celecoxib is classified as class II in the biopharmaceutics categorisation system (BCS). After oral treatment, celecoxib's low water solubility causes significant absorption variability. In order to combat gout, this study sought to create a celecoxib self-nanoemulsifying drug delivery system (SNEDD). Sesame oil, span 80, and PEG 400 were used to create the pseudo-ternary phase diagram that was used to optimise the SNEDDS formulation. Surface response design was utilised to optimise the formulation, and the resultant C-SNEDDs formulation demonstrated a 100% transmittance, a small globule size of 100.5 nm, and high solubility up to 133.6. According to in vitro release experiments, the formulation's celecoxib release was high and quick. In contrast to traditional tablets, the self nanoemulsifying drug delivery system (SNEDDS), which uses celecoxib as a model drug, was found to achieve an effective therapeutic concentration and is intended to reduce the risk of heart attacks by reducing the dosage and relieving pain related to inflammation with a single dose. Zero-order and first-order drug release kinetics were demonstrated by C-SNEDDS in vitro release. With improved solubility, the created formulation was found to be superior to pure celecoxib, indicating that a lipidic system is an effective drug delivery method for treating gout.